Fine-Kinney Risk Assessment Integrated With Fuzzy Based SWARA and VIKOR Methods: A Case Study in Paint Industry - HACIBEKTAŞOĞLU, SÜLEYMAN ENES (My University, 2021)
Occupational health and safety activities implemented in the workplaces aim to ensure that employees are in a state of spiritual and physical well-being. In this context, it is significant to identify the existing hazards in the workplaces with a proactive approach, to identify the risks arising from these hazards and to reduce the risk level to an acceptable level by taking the necessary measures. There are various risk analysis methods for this purpose in the workplaces. Within the scope of this study, the classical Fine-Kinney risk analysis method, which is widely used in our country, was modeled for a workplace in the paint industry using fuzzy logic based multi-criteria decision making methods. Criteria significance levels calculated with the SWARA by the help of decision makers who are experts in Occupational Safety were determined by weighting the probability, severity and frequency in the classical Fine-Kinney method. Then, fuzzy logic based VIKOR method was used to complete the analysis. With this determined integrated method, it is aimed to eliminate the errors and uncertainties arising from numerical valuation performed in the classical method. Contrary to the classical method, the criteria are expressed in linguistic terms in the new method. Converting to numeric expressions is done with fuzzy logic and the errors that may occur are tried to be minimized. As a result of the study, an increase in the sensitivity of the results was observed due to the using fuzzy logic. In addition, changes were determined in risk priority scores. Keywords: Fine-Kinney, risk assessment, fuzzy logic, multi criteria decision making.
Keywords: Fine-Kinney; risk assessment; fuzzy logic; multi criteria decision making